Perancangan Ui/Ux Website Promosi Dan Penjualan Di Maripro Photo Studio Dengan Menggunakan Metode Human Centered Desain - Haykal Zulfadli; Randi Rian Putra; Hermansyah (Jurnal Nasional Teknologi Komputer, 2025)
The development of science and technology has encouraged every sector to utilize information quickly, precisely, and accurately. In the creative service industry, the utilization of information technology such as websites is an important strategy to increase promotion and sales. Maripro Photo Studio, as a local photography business in Medan, is still limited in digital marketing because it only relies on WhatsApp and Instagram. This research aims to design the user interface (UI) and user experience (UX) of a promotional and sales website based on the Human Centered Design (HCD) approach. This method consists of five stages, namely observation, definition, ideation, prototyping, and testing, which are focused on the needs and comfort of end users. Data was collected through direct observation, interviews with the studio, and literature studies related to UI/UX design and digital marketing. The results of the design process show that the website has an attractive appearance, easy navigation, and is able to convey information effectively. Evaluation through usability testing on users shows a high average score on the aspects of ease of use, aesthetics, accessibility, and user satisfaction. In conclusion, this website can be a digital solution that increases the marketing reach and service quality of Maripro Photo Studio. In addition, the results of this study can also be used as a reference in the development of similar systems in the industry sector.